Work efficiency in a small garment company - Elegado, Anna Leticia O.
The study determined the work efficiency through time and motion study in a small garment company. The measurements were conducted in the cutting, sewing, finishing and pressing departments of the small garment company. Significant results were shown in the percentage efficiency of the work which ranged from 66% to 103%. There is a varying amount of work efficiency in the company which was further studied in the motion study part of the research. In the motion study, observations were used as a basis for the measurement. Recommendations were given to improve the work efficiency and a revised plant layout was made for a more efficient flow of work.